Media, modernity, and dynamic plants in early 20th century German culture - Janzen, Janet Lindeblad. (Critical Plant Studies, 2016)
In Media, Modernity and Dynamic Plants , Janet Janzen traces the motif of the "dynamic plant" through film and literature in early 20th century German culture. Often discussed solely as symbols or metaphors of the human experience, plants become here the primary focus and their role in literature and film is extended beyond their symbolic function. Plants have been (and still are) seen as closer to static objects than to living, moving beings. Making use of examples from film and literature, Janet Janzen demonstrates a shift in the perception of plants-as-objects to plants-as-living-beings that can be attributed to new technology and also to the return of Romantic and Vitalistic discourses on nature.